CACNA1C (rs1006737) may be a susceptibility gene for schizophrenia: An updated meta‐analysis. Issue 6 (29th April 2019) - Zhu, Dongjian; Yin, Jingwen; Liang, Chunmei; Luo, Xudong; Lv, Dong; Dai, Zhun; Xiong, Susu; Fu, Jiawu; Li, You; Lin, Juda; Lin, Zhixiong; Wang, Yajun; et al.
Abstract: Introduction: Schizophrenia is a serious mental illness with a genetic predisposition. Genome‐wide association studies (GWAS) have identified the α‐1C subunit of the L‐type voltage‐gated calcium channel ( CACNA1C ) gene as a significant risk gene for schizophrenia. However, there are inconsistent conclusions in case–control studies. Methods: We performed a comprehensive meta‐analysis of all available samples from existing studies under four different genetic models (recessive model, dominant model, additive model and allele model) to further confirm whether CACNA1C rs1006737 is an authentic risk single nucleotide polymorphism (SNP) for schizophrenia. Results: A statistically significant difference under the four models (all p < 0.05) was observed by pooling nine Asian and European studies, including a total of 12, 744 cases and 16, 460 controls. For European‐decent samples, a significant difference was identified between patients and controls for the four models (all p < 0.05). We observed a significant difference between patients and controls for the recessive model and allele model (GG vs. GA + AA: p < 0.00001; G vs. A: p < 0.00001) using a fixed effect model, but the dominant model (GG + GA vs. AA: OR: p = 0.15) and additive model (GG vs. AA: p = 0.11) showed no significant difference between patients and controls in the Asian samples. Conclusion: Our findings provide important evidence for the establishment of CACNA1C as a susceptibility gene for schizophrenia across world populations, but its roles in the pathogenesis of schizophrenia need to be further investigated. Abstract : We conducted a meta‐analysis integrating nine studies under four different genetic models to evaluate the association of rs1006737 in the CACNA1C gene with schizophrenia. Our findings provide important evidence for the establishment of CACNA1C as a susceptibility gene for schizophrenia across world populations.